EFEKTIVITAS BELAJAR MENGAJAR MENYENANGKAN DENGAN APLIKASI QUIZIZZ DI TENGAH PANDEMI COVID-19 - Talkah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
Abstract: Android users and are able to operate multimedia functions on Android to play games and the internet, and social media only so that the use of the learning process is minimal. While currently there are many applications or those that can be used in learning, they are interactive games. In the use of interactive media, learning is said to be very helpful in the course of the learning process activities in the classroom, especially in increasing student learning achievement, so that it can overcome the saturation of students in the learning process and can improve the quality of student learning much better in terms of the learning process and the learning outcomes of students. This article contains a discussion related to the use of the Quizizz application with the observation method of several high school students in Surabaya and then analyzed with relevant theories. In utilizing the effectiveness of teaching and learning using the Quizizz application it can increase student learning concentration and can increase enthusiasm for learning amid the Covid-19 pandemic. so learning online feels more fun and students can learn while playing through this Quizizz application. Where students can see the ranking directly on the leaderboard at the end of the quiz, that way students continue to want to try the learning quiz test that has been given by the teacher which is in accordance with the subject area taught and can help educators in evaluating learning with more creative and teaching methods. new.